Effects of salt type on the metabolites and microbial community in kimchi fermentation. Issue 11 (November 2022) - Lee, Mi-Ai; Choi, Yun-Jeong; Kim, Ye-Sol; Chon, Seo-Yeong; Chung, Young Bae; Park, Sung-Hee; Yun, Ye-Rang; Min, Sung Gi; Yang, Ho-Chul; Seo, Hye-Young
Abstract: The taste of kimchi is greatly affected by the salt type used during fermentation. Here, we investigated the effects of salts with different mineral contents on the microbial community and metabolite profiles of fermented kimchi using multivariate statistical analysis. We evaluated different types of salt used to prepare kimchi, namely, solar salt aged for 1 year, solar salt aged for 3 years, dehydrated solar salt, and purified salt. The main microorganisms detected in kimchi were Weissella koreensis, Leuconostoc mesenteroides, and Latilactobacillus sakei . Leuconostoc and Weissella were mainly present in kimchi supplemented with solar salt. However, a high proportion of L. sakei was present in kimchi supplemented with purified salt and dehydrated salt. Additionally, using GC-MS-based metabolite analysis, we revealed that the content of free sugars, organic acids, and amino acids differed in kimchi fermented with different salt types. Therefore, we demonstrated that salt type had a pronounced effect on the resultant microbial community and the type and concentration of metabolites present in fermented kimchi. Abstract : Kimchi; Solar salt; Metabolites; Microbial community; Lactic acid bacteria.